STUDI EFEKTIFITAS PENGGUNAAN JEJARING SOSIAL SEBAGAI PENUNJANG PROSES PEMBELAJARAN PADA MAHASISWA FAKULTAS TEKNOLOGI INFORMASI DAN KOMUNIKASI USM - Robby Kurniawan Budhi; Vensy Vydia; Maya Rini Handayani (Jurnal Transformatika, 2011)
Social network developing as medium of communication was effloresce quick. Accompanying sites as Facebook have become tren and one wills be main requirement for one any one. And so do thing it among civitas Technological Faculty academic person Information and semarang University Communication (FTIK USM). Among college student, Facebook is accessed everyday and bermunculan's community group. One of it is group "FTIK semarang University". All this time, oftentimes that group is utilized as media of academic information conveyor and also another information of lecturer goes to college student or even contrariwise. In this research, done by penelusuran opinion by use of kuesioner online ala that is broadcast to all college student and group member lecturer "FTIK Semarang University". Of that kuesioner's result, wait for it will know group purpose effectiveness as media of information conveyor.